Beyond Monopoly: Enhancing SME Branding Knowledge through Board Game Experiences - Anggrianto, Christian; Sidharta, Helena (VCD, 2024)
In the era of rapid technological advancements and ever-changing consumer behaviors, small and medium enterprises (SMEs) face the challenge of keeping up with the complexities of branding in the competitive market landscape. This study delves into the innovative use of board games as an educational tool to enhance SMEs' understanding of branding concepts, mainly targeting entrepreneurs with limited formal education. Drawing on experiential learning and gamification principles, the research investigates the impact of board games designed specifically for SMEs. These games, tailored to address businesses’ unique challenges with limited educational resources, provide entrepreneurs with a dynamic and interactive platform to explore branding strategies, brand identity development, and customer engagement techniques. Through workshops and in-depth case studies, the research assesses the effectiveness of board games in facilitating active learning and knowledge retention among SME owners and managers. Preliminary findings reveal that the immersive and engaging nature simplifies complex branding concepts and fosters a collaborative learning environment, enabling participants to experiment with diverse strategies in a risk-free setting. This research advocates integrating gamified learning strategies into formal and informal SME training programs. The findings underscore the potential of innovative, interactive methods in democratizing access to branding knowledge and nurturing the growth of SMEs in competitive markets. By bridging the gap between theoretical knowledge and practical application, board games emerge as a promising instrument for enhancing the branding capabilities of SMEs, thereby promoting their sustainable growth and competitiveness in the market.